Comparison of the effects of modified pectoral nerve block and erector spinae plane block on postoperative opioid consumption and pain scores of patients after radical mastectomy surgery: A prospective, randomized, controlled trial - Altıparmak, Başak; Korkmaz Toker, Melike; Uysal, Ali İhsan; Turan, Mustafa; Gümüş Demirbilek, Semra (Journal of clinical anesthesia, 2019)
Breast cancer is the most common malignancy of women all over the world. In this study, we compared the effects of ultrasound-guided modified pectoral nerve (PECS) block and erector spinae plane (ESP) block on postoperative opioid consumption, pain scores, and intraoperative fentanyl need of patients undergoing unilateral modified radical mastectomy surgery. Single-blinded, prospective, randomized, efficacy study. Tertiary university hospital, postoperative recovery room and surgical ward. Forty patients (ASA I–II) were allocated to two groups. After exclusion, 38 patients were included in the final analysis (18 patients in the PECS groups and 20 in the ESP group). Modified pectoral nerve block was performed in the PECS group and erector spinae plane block was performed in the ESP group. Postoperative tramadol consumption and pain scores were compared between the groups. Also, intraoperative fentanyl need was measured. Postoperative tramadol consumption was 132.78 ± 22.44 mg in PECS group and 196 ± 27.03 mg in ESP group (p = 0.001). NRS scores at the 15th and 30th min were similar between the groups. However, median NRS scores were significantly lower in PECS group at the postoperative 60th min, 120th min, 12th hour and 24th hour (p = 0.024, p = 0.018, p = 0.021 and p = 0.011 respectively). Intraoperative fentanyl need was 75 mg in PECS group and 87.5 mg in ESP group. The difference was not statistically significant (p = 0.263). Modified PECS block reduced postoperative tramadol consumption and pain scores more effectively than ESP block after radical mastectomy surgery. •Two thirds of women were found to develop chronic pain after breast cancer surgery.•PECS block reduced postoperative tramadol consumption more effectively than ESP block.•PECS block reduced postoperative pain scores more effectively than ESP block.•Both PECS block and ESP blocks are effective for analgesia after mastectomy surgery.